Participation, information giving and decision making in different communication styles during medical consultations - Haron, Nurul Nadia (2014)
Patients‟ participation and doctor‟s information giving are two important components within medical consultations. Research has shown that both components are influenced by the communication style adopted by doctors during medical consultations. This will consequently affect the decision made at the end of the consultations. Therefore, this study aims to look at how communication style affects the three important inter-related components in clinical consultation which are patients‟ participation, information provision and decision making. Respondents for this study consist of patients and doctors at a Haematology Clinic in a government hospital in Malaysia. The data gathered for this study involves audio-recordings from authentic clinical consultations. This study adopts a discourse analytic approach based on the components of patient‟s participation for the first stage of analysis while the second stage analysis involves the Roter‟s Interaction Analysis System (RIAS). The findings suggest that there are two types of communication style used by the doctors during the consultations which are the directing and sharing consultation styles. The data analysis in the sharing consultation style showed higher patients' participation and higher information giving by the doctor, and these resulted in a more shared decision making at the end. The type of communication style used by the doctors can affect the outcome of the consultation. The findings of this study have important implications on appropriate consultation style and provide a guideline on improving communication during consultations at the Haematology Clinic.